Carbon fiber composite material and preparation method thereof

By introducing metal energy-absorbing layers and multi-layer structures into carbon fiber composites, the problem of the material being prone to break under impact is solved, and the impact resistance and service life are significantly improved.

CN119748984AActive Publication Date: 2025-04-04JIANGSU AOSHENG COMPOSITE MATERIALS HI TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510042043.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing carbon fiber composite materials are prone to breaking or cracking during impact or severe deformation, and there are problems of material fatigue or damage, resulting in degradation of performance.

Method used

A composite material structure consisting of a metal energy absorbing layer, a thermosetting resin layer, a carbon fiber layer and a thermoplastic resin layer are adopted, and the metal energy absorbing layer is composed of foam metal, carbon fiber and foam resin, and is prepared by a hot pressing curing process.

Benefits of technology

It significantly improves the impact resistance and service life of carbon fiber composite materials, enhances the toughness and energy-absorbing properties of the materials, and avoids the risk of material damage under impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005238609050000081
    Figure BDA0005238609050000081
  • Figure BDA0005238609050000084
    Figure BDA0005238609050000084
  • Figure BDA0005238609050000091
    Figure BDA0005238609050000091
Patent Text Reader

Abstract

The invention relates to a carbon fiber composite material and a preparation method thereof.The carbon fiber composite material comprises a metal energy absorption layer, a thermosetting resin layer, a carbon fiber layer and a thermoplastic resin layer which are sequentially arranged, and raw materials of the metal energy absorption layer comprise foam metal, carbon fibers and foaming resin; raw materials of the thermosetting resin layer comprise thermosetting resin, a curing agent and an elastomer, raw materials of the carbon fiber layer comprise carbon fibers, and raw materials of the thermoplastic resin layer comprise thermoplastic resin. According to the carbon fiber composite material provided by the invention, the metal energy absorption layer, the thermosetting resin layer, the carbon fiber layer and the thermoplastic resin layer are subjected to layer-by-layer toughening, so that the energy absorption performance of the carbon fiber composite material is effectively improved, carbon fibers are effectively supported, a cushioning effect is provided for the carbon fibers, damage caused by ultrahigh-strength impact is prevented, and the service life of the material is prolonged; the carbon fiber composite material is used in the field of energy absorption and noise reduction, and has better impact resistance and tensile strength, the preparation process is pollution-free, and large-scale production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carbon fiber composite material preparation, and specifically relates to a carbon fiber composite material and a preparation method thereof. Background Art

[0002] With the continuous evolution of science and technology and the changes in market demand, energy-absorbing materials will continue to move towards higher performance, greater intelligence and greater eco-friendliness; the excellent performance of the material is particularly critical in the fields of aerospace, automobiles, sports equipment and civil construction, such as shock absorption, impact protection and noise absorption; in order to meet the needs of the rapid development of energy absorption and noise reduction in my country, it is urgent to develop high-performance energy-absorbing and seismic-resistant materials to serve social development.

[0003] Carbon fiber materials are widely used in the fields of energy absorption and noise reduction, involving many fields such as aerospace, automobiles, sports equipment and civil construction. Carbon fiber has the characteristics of lightweight, high specific strength, high specific modulus, high temperature resistance, corrosion resistance, fatigue resistance, etc. These properties give it superior energy absorption characteristics when subjected to dynamic loads. Although carbon fiber has excellent strength and stiffness, carbon fiber reinforced composites may show brittleness in some cases. They may easily break or crack when subjected to impact or severe deformation; combining porous materials with carbon fiber materials can improve the toughness of carbon fiber materials, change their brittleness, and make up for the shortcomings of the substrate performance.

[0004] For example, patent CN113276523B discloses a PBO fiber / aramid fiber reinforced composite material and a preparation method thereof. The face plate of the composite material is a PBO fiber reinforced thermosetting resin composite material, and the back plate is an aramid fiber reinforced thermoplastic resin composite material. The composite material relies on the properties of aramid itself to absorb energy, and there are problems of material fatigue or damage, which leads to a decrease in various aspects of material performance. Summary of the invention

[0005] The object of the present invention is to provide an improved carbon fiber composite material with excellent impact resistance, high strength and long service life.

[0006] The present invention also provides a method for preparing the carbon fiber composite material, and the preparation process is simple.

[0007] In order to achieve the above object, a technical solution adopted by the present invention is:

[0008] A carbon fiber composite material comprises a metal energy absorbing layer, a thermosetting resin layer, a carbon fiber layer, and a thermoplastic resin layer which are arranged in sequence. The raw materials of the metal energy absorbing layer comprise foamed metal, carbon fiber, and foamed resin. The raw materials of the thermosetting resin layer comprise thermosetting resin, a curing agent, and an elastomer. The raw materials of the carbon fiber layer comprise carbon fiber. The raw materials of the thermoplastic resin layer comprise thermoplastic resin.

[0009] In some preferred embodiments of the present invention, the foam metal is a combination of one or more selected from foam aluminum, foam copper, foam nickel, foam aluminum, and foam magnesium. Compared with general sintered porous metals, the foam metal has a higher porosity. The foam metal refers to a metal material containing foam-like pores. Since the foam metal is a two-phase composite material composed of a metal matrix skeleton continuous phase and a pore dispersed phase or continuous phase, the properties of the foam metal depend on the metal matrix used, the porosity and the pore structure, and are affected by the preparation process.

[0010] According to some specific aspects of the present invention, the foam metal is preferably foam aluminum, which can meet the requirements of excellent mechanical properties and energy absorption effect as well as compatibility with foaming resin.

[0011] According to some specific aspects of the present invention, the porosity of the foam metal is 30-80%, and the porosity refers to the percentage of the pore volume in the bulk material to the total volume of the material in a natural state, and the porosity is tested according to GB / T10799-2008 standard.

[0012] According to some specific aspects of the present invention, the porosity of the foam metal is preferably 40-80%, and the mechanical properties of the foam metal decrease with the increase of the porosity. When it is subjected to pressure, the increase in the stress-bearing area caused by the collapse of the pores and the strain hardening effect of the material make the foam metal have excellent impact energy absorption characteristics.

[0013] According to some specific aspects of the present invention, the average pore size of the foam metal is 1-10 mm, and the average pore size is the cross-sectional diameter of the pores in the foam metal layer, which is measured by photographing the cross section with a scanning electron microscope.

[0014] According to some specific aspects of the present invention, the average pore size of the foam metal is preferably 1-5 mm, so that the materials filled into the foam metal layer can be evenly mixed.

[0015] According to some specific aspects of the present invention, the volume density of the foam metal is 0.1-1.5 g / cm 3 Volume density refers to the mass of a material per unit volume (including the material entity and its open pores and closed pores) in its natural state, commonly known as bulk density. The more pores per unit volume, the smaller the volume density.

[0016] According to some specific aspects of the present invention, the volume density of the foam metal is preferably 0.5-1.0 g / cm 3 , the material is lighter.

[0017] According to some specific aspects of the present invention, the thickness of the foam metal is 1-50 mm, and the thickness is tested by a thickness gauge. The thickness of 9 different places on the foam metal layer is measured and the average value is taken as the thickness of the foam metal layer.

[0018] According to some specific aspects of the present invention, the thickness of the foam metal is preferably 1-30 mm, and the composite material has better impact resistance and lightness.

[0019] According to some specific aspects of the present invention, the tensile strength of the foam metal is 1-15 MPa. The tensile strength is tested according to GB / T 1040.1-2018.

[0020] According to some specific aspects of the present invention, the tensile strength of the foam metal is preferably 5-12 MPa, and the tensile strength of the composite material is even better.

[0021] In some preferred embodiments of the present invention, the carbon fiber raw material of the metal energy absorbing layer is powder, and the average fiber length of the carbon fiber of the metal energy absorbing layer is 0.1-5mm. Carbon fiber powder is an isotropic cylindrical particle obtained by surface treatment, grinding, microscopic screening, screening, and high-temperature drying of high-strength and high-modulus carbon fiber filaments with special technology. It retains many excellent properties of carbon fiber, and has a small shape and a pure surface. It is easy to be wetted and evenly dispersed by resin, and is a composite material filler with excellent performance; its fiber length refers to the distance between the two ends of the fiber measured when it is straightened without the influence of external force. Generally speaking, under the same fiber volume fraction and fiber length distribution, the larger the fiber length, the better the mechanical properties of the composite material, such as elastic modulus, strength and fracture toughness.

[0022] According to some specific aspects of the present invention, the average fiber length of the carbon fibers of the metal energy absorbing layer is preferably 0.5-3.5 mm, and the mixing uniformity and mechanical properties are good.

[0023] In some preferred embodiments of the present invention, the foamed resin is a combination of one or more selected from polystyrene, polyurethane, polyvinyl chloride, and polyethylene. The foamed resin is a material that produces a microporous structure through a specific process. These microporous structures give the material properties such as light weight, heat insulation, sound absorption, and shock absorption.

[0024] According to some specific aspects of the present invention, the foaming resin is preferably polyurethane, which has good stability and energy absorption performance.

[0025] In some preferred embodiments of the present invention, the raw material of the thermosetting resin layer includes a thermosetting resin, and the thermosetting resin has a large number of polar groups and is used to bond the metal energy absorbing layer and the carbon fiber layer. The thermosetting resin is a combination of one or more selected from thermosetting epoxy resins, thermosetting unsaturated polyester resins, thermosetting polyurethane resins, thermosetting phenolic resins, thermosetting urea-formaldehyde resins, thermosetting silicone resins, and thermosetting melamine-formaldehyde resins.

[0026] According to some specific aspects of the present invention, the thermosetting resin is a combination of one or more selected from thermosetting epoxy resins and thermosetting unsaturated polyester resins, which can ensure excellent strength of the composite material.

[0027] According to some specific aspects of the present invention, the thermosetting epoxy resin is a combination of one or more selected from bisphenol A epoxy resin, diphenol propane epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, epoxidized olefin compound, heterocyclic epoxy resin, and mixed epoxy resin.

[0028] According to some specific aspects of the present invention, the thermosetting unsaturated polyester resin is a combination of one or more selected from bisphenol A type vinyl unsaturated polyester, isophthalic acid type vinyl unsaturated resin, and styrene / butadiene copolymer unsaturated polyester.

[0029] According to some specific aspects of the present invention, the thermosetting resin is preferably a combination of one or more of bisphenol A epoxy resin and isophthalic acid type vinyl unsaturated resin, which is beneficial to the adhesion between the thermosetting resin layer and the metal energy absorbing layer, as well as the mechanical strength and service life of the prepared composite material.

[0030] In some preferred embodiments of the present invention, the curing agent is a polyamide curing agent, and the content of the polyamide curing agent is 5-15 parts by weight relative to 100 parts by weight of the thermosetting resin.

[0031] According to some specific aspects of the present invention, the content of the polyamide curing agent is 5-10 parts by weight, so that the curing is sufficient and the preparation time of the composite material is reduced.

[0032] According to some specific aspects of the present invention, the elastomer includes a polyamide elastomer, wherein the content of the polyamide elastomer is 5-15 parts by weight relative to 100 parts by weight of the thermosetting resin, so that the thermosetting resin layer has better toughness.

[0033] According to some specific aspects of the present invention, the polyamide elastomer is a combination of one or more selected from polyether block amide elastomer (PEBA), polyether ester amide (PEEA) elastomer and polyester amide (PEA) block copolymer elastomer.

[0034] According to some specific aspects of the present invention, the content of the polyetherester polyamide elastomer (PEEA) is preferably 5-10 parts by weight, which has good toughness enhancement and low cost.

[0035] In some preferred embodiments of the present invention, the carbon fibers of the carbon fiber layer are selected from a combination of one or more of carbon fiber paper, carbon fiber cloth, carbon fiber felt, and carbon fiber braid.

[0036] According to some specific aspects of the present invention, the carbon fibers of the carbon fiber layer are preferably carbon fiber braids, which have good bonding strength with the thermosetting resin layer and the thermoplastic resin layer.

[0037] According to some specific aspects of the present invention, the thickness of the carbon fiber layer is 0.1-1.5 mm, and the thickness is tested by a thickness gauge. The thickness of 9 different places on the carbon fiber layer is measured and the average value is taken as the thickness of the carbon fiber layer.

[0038] According to some specific aspects of the present invention, the tensile strength of the carbon fiber layer is greater than 3500 MPa, and the tensile strength is tested according to GB / T 1040.1-2018. The thicker the material, the stronger its tensile strength.

[0039] According to some specific aspects of the present invention, the carbon fiber layer thickness is preferably 0.1-1.0 mm, and its tensile strength is greater than 4000 MPa, which meets the strength requirements while having low cost.

[0040] In some preferred embodiments of the present invention, the thermoplastic resin is a combination of one or more selected from polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyamide, polyoxymethylene, polycarbonate, polyphenylene ether, polysulfone, rubber, and polyester.

[0041] According to some specific aspects of the present invention, the thermoplastic resin is preferably a polyamide resin, which has good bonding strength with the carbon fiber layer.

[0042] According to some specific aspects of the present invention, the polyamide resin is a polymer material containing repeating structural units of amide groups (-CO-NH-), and the polyamide resin is selected from aliphatic polyamide, semi-aromatic polyamide, and aromatic polyamide.

[0043] According to some specific aspects of the present invention, the aliphatic polyamide is a combination of one or more selected from polybutylene adipamide, polyhexamethylene adipamide, polyhexamethylene sebacamide, polyhexamethylene dodecanediamide, and polydecamethylene sebacamide.

[0044] According to some specific aspects of the present invention, the semi-aromatic polyamide is a combination of one or more selected from polybutylene terephthalamide, polybutylene furan diamine, polypentamethylene terephthalamide, polypentamethylene furan diamine, polyhexamethylene terephthalamide, polyhexamethylene furan diamine, polynonamethylene terephthalamide, polynonamethylene furan diamine, polydecamethylene terephthalamide, polydecamethylene furan diamine, polydodecamethylene terephthalamide, polydodecamethylene furan diamine, polytridecaproamide, polytridecaproamide, polyhexamethylene terephthalamide decanediamine, polyfuran dicarboxamide decanediamine, polyfuran dicarboxamide pentamethylene terephthalate, and polyfuran dicarboxamide decanediamine.

[0045] According to some specific aspects of the present invention, the aromatic polyamide is a combination of one or more selected from poly(p-phenylene terephthalamide), poly(p-phenylene furan dicarboxamide), and poly(p-phenylene terephthalate furan dicarboxamide).

[0046] According to some specific aspects of the present invention, the polyamide is preferably a semi-aromatic polyamide, and more preferably a combination of one or more of poly(decane terephthalamide) and poly(hexamethylene terephthalamide) decanediamine, which has high temperature resistance and low water absorption to maintain a long service life of the composite material.

[0047] Another technical solution provided by the present invention is:

[0048] A method for preparing the above-mentioned carbon fiber composite material, the preparation method comprising:

[0049] (1) A metal energy absorbing layer, a thermosetting resin layer, and a thermoplastic resin layer are prepared respectively, wherein:

[0050] When preparing the metal energy absorbing layer: the foamed metal and the carbon fiber are mixed and placed in a molten foaming resin, and then foamed to obtain the metal energy absorbing layer;

[0051] When preparing the thermosetting resin layer: a thermosetting resin, a curing agent and an elastomer are mixed and hot-pressed to form the thermosetting resin layer;

[0052] (2) The metal energy absorbing layer, the thermosetting resin layer, the carbon fiber layer, and the thermoplastic resin layer are arranged in sequence, and then hot-pressed and cured to prepare the carbon fiber composite material.

[0053] According to some specific aspects of the present invention, in step (1), when preparing the metal energy absorbing layer: the foamed metal is placed on the carbon fiber powder, and then placed in an ultrasonic vibrator to fully vibrate with ultrasound; at the same time, the foaming resin is melted at 150-250°C; then, the mixture of the foamed metal and the carbon fiber powder is placed in the melted foaming resin, and finally a supercritical fluid is used for foaming to obtain the metal energy absorbing layer.

[0054] According to some specific aspects of the present invention, the foaming parameters are: first, at 100-250°C and 10-20MPa supercritical CO 2 Soak in water for 1-3 hours, and then foam under steam at 100℃.

[0055] According to some specific aspects of the present invention, in step (1), when preparing the thermosetting resin layer: the thermosetting resin, curing agent and elastomer are mixed by a high-speed ball mill for 1-3 hours, and then mixed and hot-pressed at 30-60°C and 0.5-2MPa for 10-30 minutes to obtain the thermosetting resin layer.

[0056] According to some specific aspects of the present invention, the prepared metal energy absorbing layer, thermosetting resin layer, carbon fiber layer and thermoplastic resin layer are cured by vacuum hot pressing to obtain a carbon fiber composite material.

[0057] In some preferred and specific aspects of the present invention, in step (2), the thermoplastic resin layer is first heated to 200-250°C, and then the carbon fiber layer is attached to the thermoplastic resin layer, followed by hot pressing at 200-250°C and 0.5-2.0MPa for 5-15min, and then the thermosetting resin layer and the metal energy absorbing layer are compounded on the carbon fiber layer in sequence, and finally hot pressing at 100-150°C and 3-10MPa for 30-60min, and the carbon fiber composite material is obtained after cooling.

[0058] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0059] 1. Combining foam metal with foam resin, the pores are developed and the seismic performance of carbon fiber composite materials is enhanced in a coordinated manner;

[0060] 2. Through the interlayer toughening of the metal energy absorbing layer, thermosetting resin layer, carbon fiber layer, and thermoplastic resin layer, the energy absorption performance of the carbon fiber composite material is effectively improved, the carbon fiber is effectively supported, the carbon fiber is given a shock absorbing effect, the damage caused by ultra-high strength impact is prevented, and the service life of the material is extended;

[0061] 3. Foam metal, foam resin and carbon fiber are lightweight materials, and the prepared carbon fiber composite material is lightweight and high in strength;

[0062] 4. Carbon fiber composite materials are used in the field of energy absorption and noise reduction. Carbon fiber composite materials have excellent impact resistance and tensile strength, the preparation process is pollution-free, and they are easy to mass produce. DETAILED DESCRIPTION

[0063] The present invention is further described below in conjunction with the illustrated embodiments.

[0064] The raw materials of Examples 1-11 and Comparative Examples 1-7 are as follows.

[0065]

Foam Metal

[0066] A1: Foam aluminum, TMAX-Aluminum foam-02 foam aluminum produced by Xiamen Tianmeifu Machinery Equipment Co., Ltd., with a porosity of 68-78%, an average pore diameter of 1.6mm, and a volume density of 0.60-0.85g / cm 3 , thickness is 5-6mm, and tensile strength is 8MPa.

[0067] A2: Foam aluminum, produced by Shanghai Yinfu Hardware Products Co., Ltd., has a porosity of 60-70%, an average pore diameter of 3 mm, and a volume density of 0.4-0.5 g / cm 3 , thickness is 5-6mm, and tensile strength is 4MPa.

[0068]

Carbon fiber with metal energy absorbing layer

[0069] B1: Carbon fiber powder, T700 chopped carbon fiber produced by Toray Industries, Ltd., Japan, fiber length 2 mm.

[0070] B2: Carbon fiber powder, MLD-300 carbon fiber powder produced by Toray Industries, Ltd., Japan, with a fiber length of 130 μm.

[0071]

Foaming resin

[0072] C1: Polyethylene, LD100AC polyethylene produced by Sinopec Shanghai Petrochemical Co., Ltd.

[0073] C2: Polyurethane, FP3039D6 polyether polyurethane produced by GreenMobil.

[0074] The metal energy absorbing layer (M1) was prepared according to the formula described in Table 1. The foamed metal was placed in the carbon fiber powder and fully vibrated and ultrasonically obtained to obtain a mixture of the foamed metal and the carbon fiber. The foamed resin was then heated to 130°C, and the foamed metal and carbon fiber mixture was placed in the molten foamed resin. The mixture was heated to 130°C and 15 MPa of supercritical CO. 2 The sample was immersed in water for 2 hours, then foamed in steam at 100°C, and the metal energy absorbing layer was obtained after cooling.

[0075] The metal energy absorbing layer (M2-M4) was prepared according to the formula described in Table 1. The foamed metal was placed in the carbon fiber powder and fully vibrated and ultrasonically obtained to obtain a mixture of the foamed metal and the carbon fiber. The foamed resin was then heated to 200°C. The foamed metal and the carbon fiber mixture were then placed in the molten foamed resin and heated at 200°C and 15MPa supercritical CO. 2 The sample was immersed in water for 2 hours, then foamed in steam at 180°C, and the metal energy absorbing layer was obtained after cooling.

[0076] The metal energy absorbing layer (M6) was prepared according to the formula described in Table 1. The foamed metal was placed in the molten foaming resin and heated at 200°C and 15MPa supercritical CO. 2 The sample was immersed in water for 2 hours, then foamed in steam at 180°C, and the metal energy absorbing layer was obtained after cooling.

[0077] The metal energy absorbing layer (M7) is prepared according to the formula described in Table 1. The foamed metal is placed in the carbon fiber powder and fully vibrated and ultrasonically obtained to obtain a mixture of the foamed metal and the carbon fiber. The foamed resin is then heated to 200°C, and the foamed metal and the carbon fiber mixture is then placed in the molten foamed resin. The metal energy absorbing layer is obtained after cooling.

[0078] Table 1 Formula of metal energy absorbing layer

[0079] Metal energy absorbing layer Foam metal layer Carbon Fiber Foaming resin M1 A1 B1 C1 M2 A2 B1 C1 M3 A2 B2 C1 M4 A2 B1 C2 M5 A2 - - M6 A2 - C1 M7 A2 B1 C1 (C1 not foamed)

[0080]

Thermosetting resin

[0081] D1: Thermosetting epoxy resin, EPICLON3050 bisphenol A epoxy resin produced by Dainippon Ink Co., Ltd.

[0082] D2: Thermosetting unsaturated polyester resin, TZ-470 isophthalic acid type vinyl unsaturated resin produced by Jinan Changhua Resin Chemical Co., Ltd.

[0083]

Curing agent

[0084] E: Polyamide curing agent, H300 polyamide curing agent produced by Wuxi Pinhua Chemical Co., Ltd.

[0085]

Elastomer

[0086] F: Polyamide elastomer, PEBAX 7233SP01 polyetherester polyamide elastomer produced by Arkema.

[0087] The thermosetting resin layer (N1-N6) is prepared by weighing the thermosetting resin, polyamide curing agent, and polyamide elastomer according to the formula shown in Table 2, and then mixing the thermosetting resin, polyamide curing agent, and polyamide elastomer using a high-speed ball mill for 0.5-1.5 hours, and then hot pressing at 30-60°C and 0.5-2MPa for 10-30 minutes to obtain a thermosetting resin layer.

[0088] Table 2 Formulation of thermosetting resin layer (N1-N6)

[0089]

[0090]

[0091]

Carbon fiber layer

[0092] G1: Carbon fiber braid, TRK510 M carbon fiber braid produced by Mitsubishi Chemical, with a thickness of 0.57mm and a tensile strength of 4500MPa.

[0093] G2: Carbon fiber braid, TR3110 M carbon fiber braid produced by Mitsubishi Chemical, with a thickness of 0.23mm and a tensile strength of 3800MPa.

[0094]

Thermoplastic resin

[0095] H1: Polydecane terephthalamide, produced by Kingfa Technology 62G30HST2 Polydecane terephthalamide.

[0096] H2: Poly(hexamethylene terephthalamide adipate) decanediamine, produced by Kingfa Technology 42G30HS Poly(hexamethylene terephthalamide adipate) decanediamine.

[0097] The formulations of Examples 1-11 and Comparative Examples 1-7 are shown in Table 3 below.

[0098] Table 3 Formulations of carbon fiber composite materials of Examples 1-11 and Comparative Examples 1-7

[0099]

[0100]

[0101] In Examples 1-11 and Comparative Examples 5-7, according to the formula described in Table 3, the thermoplastic resin layer is heated to 200-250°C in a mold, and then the carbon fiber layer is attached to the thermoplastic resin layer, and hot pressed at 200-250°C and 0.5-2.0MPa for 5-15min. Then, the thermosetting resin layer and the metal energy absorption layer are compounded on the carbon fiber layer in sequence, and then hot pressed at 100-150°C and 3-10MPa for 30-60min. After cooling, a carbon fiber composite material with a thickness of 10±0.5mm is obtained.

[0103] Comparative Example 1: According to the formula described in Table 3, the thermoplastic resin layer is heated to 200-250°C in a mold, and then the carbon fiber layer is attached to the thermoplastic resin layer, and hot pressed at 200-250°C and 0.5-2.0 MPa for 5-15 min, and a thermosetting resin layer is composited on the carbon fiber layer, and then hot pressed at 100-150°C and 3-10 MPa for 30-60 min. After cooling, a carbon fiber composite material with a thickness of 5±0.5 mm is obtained.

[0104] Comparative Example 2: According to the formula in Table 3, the thermoplastic resin layer is heated to 200-250°C in a mold, and then the carbon fiber layer is attached to the thermoplastic resin layer, and hot pressed at 200-250°C and 0.5-2.0MPa for 5-15min, and a metal energy-absorbing layer is composited on the carbon fiber layer, and then hot pressed at this temperature for 30-60min and a pressure of 3-10MPa. After cooling, a carbon fiber composite material with a thickness of 10±0.5mm is obtained.

[0105] Comparative Example 3: According to the formula in Table 3, the thermoplastic resin layer is heated to 200-250°C in a mold, and then the thermosetting resin layer is attached to the thermoplastic resin layer, and hot pressed at 200-250°C and 0.5-2.0MPa for 5-15min, a metal energy absorbing layer is composited on the thermosetting resin layer, and then hot pressed at 100-150°C and 3-10MPa for 30-60min, and a carbon fiber composite material with a thickness of 10±0.5mm is obtained after cooling.

[0106] Comparative Example 4: According to the formula in Table 3, the carbon fiber layer, the thermosetting resin layer, and the metal energy absorbing layer are compounded in sequence, hot pressed at a temperature of 100-150°C for 30-60min and a pressure of 3-10MPa, and after cooling, a carbon fiber composite material with a thickness of 10±0.5mm is obtained.

[0107] Performance Testing

[0108] The following tests were performed on the carbon fiber composite materials of Examples 1-11 and Comparative Examples 1-7. Unless otherwise specified, each test was performed at 25° C. The main indicators are as follows:

[0109] 1. Destructive impact strength: refer to ASTM D7136-2007. Use Instron9350 fully automatic drop hammer impact tester for testing, the total weight of the drop hammer is 1±0.05kg, and the diameter of the impact head is 3±0.1mm. Each group of samples starts the test with a kinetic energy of 100J, and a gradient of 10J until the sample is destroyed to obtain the destructive impact strength of the sample;

[0110] 2. Tensile strength: Tested according to GB / T 1040.1-2018, the specimen is stretched at a rate of 5 mm / min, and the specimen size is 100 mm × 10 mm;

[0111] 3. Interlaminar shear failure stress: Tested according to the test method of GB / T28889-2012, stretching the specimen at a rate of 5 mm / min.

[0112] Table 4 Performance test data of carbon fiber composite materials of Examples 1-11 and Comparative Examples 1-7

[0113]

[0114] As shown in Table 4, compared with Comparative Examples 1-2 and 5-7, the carbon fiber composite material of Example 1 has better impact strength, tensile strength, and interlaminar shear stress than Comparative Examples 1-2 and 5-7. Compared with Comparative Examples 3-4, the carbon fiber composite material of Example 1 has better impact strength, tensile strength, and interlaminar shear stress than Comparative Examples 3-4.

[0115] In summary, compared with the composite materials of Examples 1-11 and Comparative Examples 1-7, the composite materials prepared in Examples 1-11 have better impact resistance and tensile strength; the composite materials prepared in Examples 1-11 have superior performance, and the preparation process is pollution-free, which is convenient for large-scale production.

[0116] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A carbon fiber composite material, characterized in that: It comprises a metal energy absorbing layer, a thermosetting resin layer, a carbon fiber layer and a thermoplastic resin layer which are arranged in sequence. The raw materials of the metal energy absorbing layer comprise foamed metal, carbon fiber and foamed resin. The raw materials of the thermosetting resin layer comprise thermosetting resin, curing agent and elastomer. The raw materials of the carbon fiber layer comprise carbon fiber. The raw materials of the thermoplastic resin layer comprise thermoplastic resin.

2. The carbon fiber composite material according to claim 1, characterized in that: The foam metal is a combination of one or more selected from foam aluminum, foam copper, foam nickel, foam aluminum, and foam magnesium.

3. The carbon fiber composite material according to claim 1, characterized in that: The porosity of the foam metal is 30-80%; and\or the volume density of the foam metal is 0.1-1.5 g / cm 3 ; and\or the thickness of the foamed metal is 1-50mm; and\or the tensile strength of the foamed metal is 1-15MPa.

4. The carbon fiber composite material according to claim 1, characterized in that: The carbon fiber raw material of the metal energy absorbing layer is powder, and the average fiber length of the carbon fiber of the metal energy absorbing layer is 0.1-5mm.

5. The carbon fiber composite material according to claim 1, characterized in that: The foaming resin is selected from one or more combinations of polystyrene, polyurethane, polyvinyl chloride and polyethylene.

6. The carbon fiber composite material according to claim 1, characterized in that: The elastomer includes a polyamide elastomer, wherein the content of the polyamide elastomer is 5-15 parts by weight relative to 100 parts by weight of the thermosetting resin; and\or, the curing agent includes a polyamide curing agent, wherein the content of the polyamide curing agent is 5-15 parts by weight relative to 100 parts by weight of the thermosetting resin.

7. The carbon fiber composite material according to claim 1, characterized in that: The thermosetting resin is selected from one or more of thermosetting polyurethane resin, thermosetting phenolic resin, thermosetting urea-formaldehyde resin, thermosetting organic silicon resin and thermosetting melamine-formaldehyde resin.

8. The carbon fiber composite material according to claim 1, characterized in that: The thermoplastic resin is selected from one or more combinations of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyamide, polyoxymethylene, polycarbonate, polyphenylene ether, polysulfone, rubber, and polyester.

9. The carbon fiber composite material according to claim 1, characterized in that: The carbon fibers of the carbon fiber layer are selected from one or more combinations of carbon fiber paper, carbon fiber cloth, carbon fiber felt, and carbon fiber braid; the thickness of the carbon fiber layer is 0.1-1.5 mm, and its tensile strength is greater than 3500 MPa.

10. A method for preparing a carbon fiber composite material according to any one of claims 1 to 9, characterized in that: The preparation method comprises: (1) A metal energy absorbing layer, a thermosetting resin layer, a thermoplastic resin layer, and a carbon fiber layer are prepared respectively, wherein: When preparing the metal energy absorbing layer: the foamed metal and carbon fiber are mixed and added into the molten foaming resin, and then foamed to obtain the metal energy absorbing layer; When preparing the thermosetting resin layer: a thermosetting resin, a curing agent and an elastomer are mixed and hot-pressed to form the thermosetting resin layer; (2) The metal energy absorbing layer, the thermosetting resin layer, the carbon fiber layer, and the thermoplastic resin layer are arranged in sequence, and then hot-pressed and cured to prepare the carbon fiber composite material.

Citation Information

Patent Citations

  • High-toughness antistatic epoxy resin foaming material and preparation method thereof

    CN113956613A

  • Reinforced compression-resistant anti-collision highway guardrail plate material

    CN114085490A

  • Thermoplastic / thermosetting fusion molding composite storage tank as well as preparation method and application thereof

    CN118025677A

  • Integrally recyclable carbon fiber reinforced resin-based composite material plate, preparation method and recycling method

    CN118683134A